Analysis of Reduced EEG Channels Based on Emotional Stimulus - (:unkn) unknown (IEEE, 2018)
Electroencephalogram (EEG) signals are widely used to investigate the electrical activities in the brain an to get information for these activities. In this work, samples are selected from 3 type (Negative, Neutral, Positive) emotional pictures from 'Nencki Affective Picture System' and shown to subjects. EEG signals are collected according to 10-20 international electrode system standards. Collected signals are reduced to 3 type channels (Frontal, Parieto-Occipital, Central). Power Spectral Density (PSD) of the corresponding EEG signals are investigated and separated into EEG frequency bands (Delta, Theta, Alpha, Beta). Welch Spectral Estimation Method is applied into the acquired data and their PSDs are obtained after taking the expectation of their frequencies. Using PSDs, total power is calculated for each frequency band and channel. Then ANOVA analysis is performed and statistical differences are investigated. Our analyses show that statistically significant differences exist between each frequency band and 3 type of channels and among reduced channels themselves.
Keywords: EEG; Naps; emotional states; power spectral density; Welch spectrum; Anova test